Effect of Foot Hyperpronation on Lumbar Lordosis and Thoracic Kyphosis in Standing Position Using 3-Dimensional Ultrasound-Based Motion Analysis System - Farokhmanesh, Khatere (Glob J Health Sci, 2014)
Based on clinical observations, foot hyperpronation is very common. Excessive pronation (hyperpronation) can cause malalignment of the lower extremities. This most often leads to functional and structural deficits. The aim of this study was to assess the effect of foot hyperpronation on lumbar lordosis and thoracic kyphosis. Thirty five healthy subjects (age range, 18030 years) were asked to stand on 4 positions including a flat surface (normal position) and on wedges angled at 10, 15, and 20 degrees. Sampling was done using simple random sampling. Measurements were made by a motion analysis system. For data analysis, the SPSS software (ver. 18) using paired t-test and repeated measures analysis of variance (ANOVA) was applied. The eversion created by the wedges caused a significant increase in lumbar lordosis and thoracic kyphosis. The most significant change occurred between two consecutive positions of flat surface and the first wedge. The t-test for repeated measures showed a high correlation between each two consecutive positions. The results showed that with increased bilateral foot pronation, lumbar lordosis and thoracic kyphosis increased as well. In fact, each of these results is a compensation phenomenon. Further studies are required to determine long-term results of excessive foot pronation and its probable effect on damage progression.